Pengaruh Kegiatan Melukis Terhadap Kemampuan Motorik Halus Pada Anak Pra Sekolah 4-6 Tahun - Siti Hamidah; Muhammad Saiful Rizal (Universitas Muhammadiyah Gresik, 2021)
Children's skills are closely related to motor development. Motorism is the development of controlling body movements through coordinated activities between nervous, muscle and brain structures. Motor development includes gross motor and fine motor. Both of these abilities are very important so that children can develop optimally. The research design used in this study was Pre-Experiment by using the type of research one group pre testpost test design. The population in this study was 40 students with purposive sampling sampling technique. The independent variable in this study is the painting activity while the dependent variable is fine motor development. The measuring instrument used was the denver II test and then analyzed by testing the Wilcoxon hypothesis with α = 0.05. The results of fine motor development before painting activities of 40 respondents almost entirely 28 respondents (70%) in the category of children need to get stimulation and after treatment the painting activity was almost entirely 32 respondents (80%) categorized as normal children. Wilcoxon test results showed ρ value = 0.000 ≤ α = 0.05 so that H1 was accepted. In conclusion there is the influence of painting activities on fine motor skills in pre-school children aged 4-6 years. The results of the development of fine motor skills are influenced by painting activities that help improve the development of children's creativity. So, mothers are expected to be able to train children through painting activities as a facility to develop fine motor development creativity in children.